PENGARUH METODE ECOLA BERBANTUAN MEDIA LITERACY CLOUD PADA PEMBELAJARAN MEMBACA PEMAHAMAN TEKS NARASI SD KELAS V - Pratama, Giar Anugrah; Sofyan Iskandar; Nadia Tiara Antik Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this study is to measure the difference in the average improvement of reading comprehension skills among fifth-grade students in narrative text learning, comparing those taught using the Extending Concept Through Language Activities (ECOLA) method with those taught using the Directed Reading Thinking Activity (DRTA) method. This research employed a quasi-experimental design, specifically the Nonequivalent Control Group Design. The sample consisted of 26 students from class VC and 26 students from class VD at SDN 1 Munjuljaya, Purwakarta. The results showed that students' reading comprehension skills improved by 58% after implementing the ECOLA method, with an interpretation category of